ショウワキチ ニ オケル タイキ チュウ ソダイ リュウシ ノウド ノ キセツ ヘンカ - 長田, 和雄; オサダ, カズオ; 林, 政彦; ハヤシ, マサヒコ; 原, 圭一郎; ハラ, ケイイチロウ; 矢吹, 正教; ヤブキ, マサノリ; 和田, 誠; ワダ, マコト; 塩原, 匡貴; シオバラ, マサタカ; et al. (2010)
P(論文) 昭和基地において,直径0.3 μm以上の粒径別大気エアロゾル粒子数濃度の観測をおこなった.2004年2月～ 2006年1月までの期間について,粗大粒子(直径1.0-5.0 μm)濃度の時系列変化について解析したところ,粗大粒子濃度は2-10月に高く,夏の12-1月には低かった.風速の季節変化や地理的分布,海氷縁の位置との関係,後方流跡線解析,粒径分布の季節変化から,粗大粒子数濃度の季節変化の要因について検討した.その結果,2-3月には昭和基地に近い南極沿岸域から生成した海塩粒子の寄与が大きいのに対し,海氷の最も発達する10月には,南緯60度以北の海域で生成した海塩粒子が長距離輸送されていることが示唆された. Number-size distributions (D_p>0.3 μm) of atmospheric aerosol particles were measured at Syowa Station, Antarctica, from February 2004 to January 2006. Volume concentrations of coarse particles (D_p 1.0-5.0 μm) were low in December to January and high in the rest of the year. To identify factors controlling the seasonal variation of coarse particle concentrations at Syowa Station, seasonal variations of wind speed distribution over the Southern Ocean, sea ice extent, wind speed at the edge of sea ice and at Syowa Station, and seasonal patterns of backward air trajectories were compared with the volume concentrations of coarse particles. Patterns of backward air trajectories and changes in size distributions of coarse particles associated with sea ice extent suggest changes in major source areas of sea salt particles observed at Syowa Station: coastal areas near Syowa in February and March, but far north of the sea ice edge, around 60゜ south, in October. departmental bulletin paper